Bovine Hydroxyapatite Sebagai Biomaterial Osteokonduktif Dalam Regenerasi Tulang: Sebuah Literature Review - Rony T.P. Napitupulu (Journal of Innovation Research and Knowledge, 2026)
Bovine hydroxyapatite (BHA) is a calcium phosphate-based biomaterial that has been extensively developed in bone tissue engineering due to its similarity to the mineral composition of human bone and its excellent osteoconductive properties. The development of BHA-based regenerative biomaterials has continued to advance through structural modifications, combination with polymers, and integration with modern biomaterial technologies. This literature review aims to analyze the characteristics, osteoconductive mechanisms, development of BHA-based scaffolds and bone substitutes, as well as future perspectives of BHA application in bone regeneration. A literature review method was conducted by searching scientific databases, including PubMed, Google Scholar, and ScienceDirect, using combinations of keywords related to bovine hydroxyapatite, bone regeneration, and osteoconductivity. Based on the PRISMA approach, 14 articles meeting the inclusion criteria were selected and analyzed. The results demonstrated that BHA possesses physicochemical characteristics supporting bone regeneration, including high biocompatibility, appropriate porosity, and the ability to promote osteogenic cell adhesion and proliferation. The development of BHA-based scaffolds and injectable bone substitutes combined with gelatin, hydroxypropyl methylcellulose (HPMC), alendronate, antibiotics, and ion substitution has shown improved regenerative performance. However, further studies are required regarding production standardization, long-term clinical evaluation, and the development of multifunctional biomaterials. Overall, BHA represents a promising osteoconductive biomaterial for future bone regeneration applications.